KAEDAH-KAEDAH HUKUM KEBIASAAN INTERNASIONAL YANG BERLAKU DALAM KONTRAK BISNIS INTERNATIONAL - Cindawati, Cindawati (Solusi, 2018)
The objective of the study is to analyze and describe the international customary laws applicable in international business contracts. Normative juridical research method. International Customary Law, is a legal source that can be regarded as the source of law first born in the International Trade Law of the repetitive practice of traders, in such a way that repetitive habits with such long time become binding. A customary practice of becoming binding must meet the following conditions: A practice which is repeatedly followed and followed by more than two parties (state practice): This practice is accepted as binding (opnio iuris sive necessitatis). For example, a codified habit in a freight contract is one example of FOB (Free On Board). Research result: Incoterms was established to provide a universal standard definition of terms used in national and international business transactions such as: FOB (Free On Board).